Incentives and constraints in the transformation of Punjab agriculture - McGuirk, Anya; Mundlak, Yair (International Food Policy Research Institute, 1991)
Economic growth is driven by technical change. Understanding the many factors that influence technical change is therefore key to an understanding of economic growth and its potential. Technical change has two aspects first, it has to be generated, and second, it has to be implemented. Incentives and Constraints in the Transformation of Punjab Agriculture, Research Report 87, by Anya McGuirk and Yair Mundlak, examines the factors that determined the pace of implementation of new techniques in agriculture in Punjab, India, from 1960 to 1979.It is widely recognized that new crop varieties usually take many years to fully come into use. The same is true of other new practices; for instance, the mechanization of agriculture or, more recently, cultivation under plastic. This time lapse has several explanations. Producers have to learn to grow the new varieties, or more generally, to use the new techniques, which requires information. The use of more sophisticated techniques requires human capital, and farmers with inadequate schooling will be unable to adopt them quickly. At the learning stage, there is uncertainty as to the performance of the new techniques, so farmers consider them risky and are cautious about using them. Another element of risk may be that more productive varieties sometimes perform well under very specific climatic and soil conditions, but when such conditions are not met their performance may be poor.